Prostate Cancer Magnetic Resonance Spectroscopy Imaging at 1.5 and 3.0 T: A Meta-Analysis. (August 2016) - Chen, Huiyou; Sutedjo, Janesya; Wang, Liwei; Yin, Xindao
Objective: We sought to assess the value of 1.5-T and 3-T magnetic resonance spectroscopy imaging in the diagnosis of prostate cancer by meta-analysis. Methods: Prospective studies were selected from MEDLINE, PubMed, Science Direct, OVID, and Springer between January 2004 and June 2014. Studies were reviewed based on Quality Assessment of Diagnostic Accuracy Studies criteria. Any publication bias was assessed using Deek funnel plot asymmetry test. Pooled sensitivities, specificities, positive likelihood ratios, negative likelihood ratios, and 95% confidence intervals were calculated. Summary receiver–operating characteristic curves were used to assess the results. Results: A total of 17 articles were included in this study. The area under the curve values of 1.5-T magnetic resonance spectroscopy imaging with the use of an endorectal coil, 1.5-T magnetic resonance spectroscopy imaging without the use of an endorectal coil, and 3.0-T magnetic resonance spectroscopy imaging without the use of an endorectal coil were 0.90 ± 0.03, 0.75 ± 0.03, and 0.93 ± 0.02, respectively. Conclusion: Three-tesla magnetic resonance spectroscopy imaging without the use of an endorectal coil and 1.5-T magnetic resonance spectroscopy imaging with the use of an endorectal coil both had similar applied values compared to the lower applied value of 1.5-T magnetic resonance spectroscopy imaging without the use of an endorectal coil.